LILRB4 Decrease on uDCs Exacerbate Abnormal Pregnancy Outcomes Following Toxoplasma gondii Infection - Zhan, Shaowei; Zheng, Jing; Zhang, Haixia; Zhao, Mingdong; Liu, Xianbing; Jiang, Yuzhu; Yang, Chunyan; Ren, Liqin; Liu, Zhiqiang; Hu, Xuemei (Frontiers in Microbiology, 2018)
Toxoplasma gondii (T. gondii ) infection in early pregnancy can result in miscarriage, dead fetus, and other abnormalities. The LILRB4 is a central inhibitory receptor in uterine dendritic cells (uDCs) that plays essential immune-regulatory roles at the maternal-fetal interface. In this study, T. gondii-infected human primary uDCs and T. gondii-infected LILRB4−/− pregnant mice were utilized. The immune mechanisms underlying the role of LILRB4 on uDCs were explored in the development of abnormal pregnancy outcomes following T. gondii infection in vitro and in vivo. Our results showed that the expression levels of LILRB4 on uDCs from normal pregnant mice were obviously higher than non-pregnant mice, and peaked in mid-gestation. The LILRB4 expression on uDC subsets, especially tolerogenic subsets, from mid-gestation was obviously down-regulated after T. gondii infection and LILRB4 decrease could further regulate the expression of functional molecules (CD80, CD86, and HLA-DR or MHC II) on uDCs, contributing to abnormal pregnancy outcomes. Our results will shed light on the molecular immune mechanisms of uDCs in abnormal pregnancy outcomes by T. gondii infection.